Hohner Musikinstrumente GmbH & Co. KG : break-even analysis - Hennessy, Julie; Meagher, Evan ([London] : SAGE, 2016)
This exercise is one in a series intended to help students learn how to perform financial calculations in marketing contexts. Helmut Schmidt, product manager for Hohner Musikinstrumente GmbH & Co. KG, the world's foremost manufacturer of harmonicas, accordions, melodicas, and ukuleles, was sitting at his desk reviewing his first assignment from the company's senior executive team. Schmidt had been asked to calculate the break-even point for the company's flagship product, the Marine Band harmonica, under a number of different scenarios.
Originally Published in: Hennessy, J., & Meagher, E. (2012). Hohner Musikinstrumente GmbH & Co. KG: Break-Even Analysis (Case revised 15/12/2014). 3-112-001. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Matthias Hohner AG; Break-even analysis -- Case studies